Results from the IAEA benchmark of spallation models - Khandaker, M.M.; Michel, R.; Leray, S.; David, J.C.; Konobeyev, A.; Mank, G.; Mengoni, A.; Otsuka, N.; Filges, D.; Gallmeier, F. (2011)
Spallation reactions play an important role in a wide domain of applications. In the simulation codes used in this field, the nuclear interaction cross-sections and characteristics are computed by spoliation models. The International Atomic Energy Agency (IAEA) has recently organised a benchmark of the spoliation models used or that could be used in the future into high-energy transport codes. The objectives were, first, to assess the prediction capabilities of the different spoliation models for the different mass and energy regions and the different exit channels and, second, to understand the reason for the success or deficiency of the models. Results of the benchmark concerning both the analysis of the prediction capabilities of the models and the first conclusions on the physics of spoliation models are presented.